Metamorphic record of the Asemi‐gawa eclogite unit in the Sanbagawa belt, southwest Japan: Constraints from inclusions study in garnet porphyroblasts. (31st October 2018) - Taguchi, Tomoki; Enami, Masaki; Kouketsu, Yui
Abstract: The Sanbagawa belt is one of the famous subduction‐related high‐pressure (HP) metamorphic belts in the world. However, spatial distributions of eclogite units in the belt have not yet satisfactorily established, except within the Besshi region, central Shikoku, southwest Japan because most eclogitic rocks were affected by lower pressure overprinting during exhumation. In order to better determine the areal distribution of the eclogite units and their metamorphic features, inclusion petrography of garnet porphyroblasts using a combination of electron probe microanalyser and Raman spectroscopy was applied to pelitic and mafic schists from the Asemi‐gawa region, central Shikoku. All pelitic schist samples are highly retrogressed, and include no index HP minerals such as jadeite, omphacite, paragonite, or glaucophane in the matrix. Garnet porphyroblasts in pelitic schists occur as subhedral or anhedral crystals, and show compositional zoning with irregular‐shaped inner segments and overgrown outer segments, the boundary of which is marked by discontinuous changes in spessartine. This feature suggests that a resorption process of the inner segment occurred prior to the formation of the outer segment, indicating discontinuous crystallization between the two segments. The inner segment of some composite‐zoned garnet grains displays Mn oscillations, implying infiltration of metamorphic fluid during the initial exhumation stage. Evidence for an early eclogite facies event was determined from mineral inclusions (e.g., jadeite, paragonite, glaucophane) in the garnet inner segments. Mafic schists include no index HP minerals in the matrix as with pelitic schists. Garnet grains in mafic schists show simple normal zoning, recording no discontinuous growth during crystal formation. There are no index HP mineral inclusions in the garnet, and thus no evidence suggesting eclogite facies conditions. Quartz inclusions in garnet of the pelitic and mafic schists show residual pressure values (∆ω1 ) of >8.5 cm −1 and <8.5 cm −1 respectively. The combination of Raman geobarometry and conventional thermodynamic calculations gives peak P – T conditions of 1.6–2.1 GPa at 460–520°C for the pelitic schists. The ∆ω1 values of quartz inclusions in mafic schists are converted to a metamorphic pressure of 1.2–1.4 GPa at 466–549°C based on Raman geothermometry results. These results indicate that a pressure gap definitely exists between the mafic schists and the almost adjacent pelitic schists, which have experienced a different metamorphic history. Furthermore, the peak P–T values of the Asemi‐gawa eclogite unit are compatible with those of Sanbagawa eclogite unit in the Besshi region of central Shikoku, suggesting that these eclogite units share a similar P–T trajectory. The Asemi‐gawa eclogite unit exists in a limited area and is composed of mostly pelitic schists. We infer that these abundant pelitic schists played a key role in buoyancy‐driven exhumation by reducing bulk rock density and strength.